2018
DOI: 10.1002/jctb.5659
|View full text |Cite
|
Sign up to set email alerts
|

Removal of phenolic compounds through overliming for enhanced saccharification of wheat straw

Abstract: BACKGROUND The deactivation of cellulases by phenolics is considered to be the main bottleneck in the saccharification of agricultural by‐products for efficient bioethanol production on a large scale. The removal of these phenolic inhibitors, produced as a result of pretreatment, is essential for an efficient saccharification process. One such process is overliming that has been mostly studied for hydrolysates of agricultural by‐products. In the present study however, solid biomass was used whereby the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Alkalis are often used for biomass detoxification through removal of phenolic compounds, mainly lignin, in order to facilitate the subsequent saccharification. [39] In our case, due to the relatively low concentration used, NaOH only partially removed the lignin. [40] The TPH derived from the solid residue did not show any colour change in response to the change in pH, which means that anthocyanins were not recovered or were degraded in polymeric form.…”
Section: Recovery Of Tph and Anthocyaninsmentioning
confidence: 58%
“…Alkalis are often used for biomass detoxification through removal of phenolic compounds, mainly lignin, in order to facilitate the subsequent saccharification. [39] In our case, due to the relatively low concentration used, NaOH only partially removed the lignin. [40] The TPH derived from the solid residue did not show any colour change in response to the change in pH, which means that anthocyanins were not recovered or were degraded in polymeric form.…”
Section: Recovery Of Tph and Anthocyaninsmentioning
confidence: 58%
“…In the case of lignocellulosic biomass, it is necessary to overcome the recalcitrance of the raw material (Daza Serna et al 2016 ) and to enhance the sugar recovery (Weinwurm et al 2012 ) while minimizing the production of inhibitory compounds such as furfural and 5-(hydroxymethyl)furfural during pretreatment (Weinwurm et al 2017 ). Detoxification for removal of inhibitory compounds can be performed by membrane separation, overliming, electrocoagulation or adsorption (Zhou et al 2013 ; Haq et al 2018 ; Wang et al 2018 ; Jeong et al 2019 ).…”
Section: Opportunities For the Production Of Erythritol In A Circular Economy Contextmentioning
confidence: 99%
“…Pre-treatment of wheat straw and estimation of lignocellulosic content was carried out according to our previous report by Haq et al (2018). For pretreatment, 2.5% sodium hydroxide (NaOH) was used for 10 min at a steaming temperature of 200 • C in specialized boiler.…”
Section: Biomassmentioning
confidence: 99%
“…Recently we have demonstrated that the removal of these phenolic compounds can significantly increase the saccharification rate (Haq et al, 2018). However, application of this process at commercial level needs studies at pilot scale which will provide a better understanding of the process.…”
Section: Introductionmentioning
confidence: 99%